Operations management - Heizer, Jay H. 4 0 16; Render, Barry; 5 (Boston : Prentice Hall, 2011)
Presents a comprehensive overview of operations management, discussing different facets such as accounting, industrial engineering, management science, and statistics, and covering ergonomics, scheduling, outsourcing, and other topics.
Includes bibliographical references and indexes.
Adult.
Keywords: 2 -- 0; 6; Production management. -- 20; 20; 2